Huangqi-Danshen decoction protects against cisplatin-induced acute kidney injury in mice - Liu, Xinhui; Gao, Liwen; Huang, Xi; Deng, Ruyu; Wu, Shanshan; Peng, Yu; Lu, Jiandong (Frontiers in Pharmacology, 2023)
Background: Acute kidney injury (AKI) induced by cisplatin remains a major impediment to the clinical application of cisplatin, necessitating urgent exploration for promising solutions.Huangqi-Danshen decoction (HDD), a Chinese herbal preparation, has been shown by our group to have a reno-protective effect in adenine-induced chronic kidney disease mice and diabetic db/db mice. However, the effect of HDD on cisplatin-induced AKI and its underlying mechanisms are unknown. Methods: The AKI model was established by intraperitoneal injection of cisplatin (20 mg/kg) in C57BL/6 mice. The mice in the treatment group were administrated with HDD (6.8 g/kg/d) for 5 consecutive days before cisplatin challenge. After 72 h cisplatin injection, blood and kidney tissue were subsequently collected for biochemical detection, histopathological evaluation, Western blot analysis, immunohistochemical staining, and terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick end labeling assay. Ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry was used to detect changes in renal metabolites. Results: The results showed that HDD significantly reduced serum creatinine and blood urea nitrogen levels and alleviated renal histopathological injury in cisplatin-induced AKI mice. And HDD treatment demonstrated a significant inhibition in apoptosis, inflammation, and oxidative stress in AKI mice. Moreover, non-target metabolomics revealed that HDD significantly restored 165 altered metabolites in AKI mice. Subsequent enrichment analysis and pathway analysis of these metabolites indicated that nicotinate and nicotinamide metabolism was the primary pathway affected by HDD intervention. Further investigation showed that HDD could up-regulate nicotinamide adenine dinucleotide (NAD +